Physicochemical Salivary Properties, Lactobacillus, Mutans Streptococci Counts And Early Childhood Caries In Preschool Children Of Colombia (2010)
ABSTRACT: Dental caries is a multifactorial disease, in which saliva has an important role. Saliva properties affect the growth of cariogenic microorganisms, so variations below threshold levels are considered risk factors for the development of dental caries. Salivary tests and microbiological counts of cariogenic bacteria are often used for clinical purposes in order to reveal problems that could explain caries development and have been evaluated in multiple studies, but these studies have mainly been carried out on adults. Thus, the aim of this study was to identify physicochemical salivary properties, mutans streptococci and Lactobacillus counts among preschool children, and their relationship with ECC in a cross-sectional study in Medellín, Colombia. Caries was determined using ICDAS criteria for a sample of 201 preschool children. Stimulated saliva samples were processed for bacterial detection, mean flow rate, pH and buffer capacity calculation. Risk variables for ECC were assessed individually and adjusted using a binary logistic regression model. The results showed that 71.14% of study subjects had ECC. Flow rate, final pH and Buffer capacity increased with age, but none of them were related to the presence of ECC. Although OR analysis detected correlations between ECC, gender, age, dental eruption stage and Lactobacillus presence, binary logistic regression analysis only showed gender and Lactobacillus as strongly associated with ECC. It can be concluded that gender and Lactobacillus presence are key variables for the presence of ECC in these children; whilst age and dental eruption stage play a minor role. Further studies are required to clarify the role of mutans streptococci counts in this population and to establish normal salivary parameters as well as threshold levels for hyposalivation in preschool children, as results showed differences with normal parameters used for adults.